Juridical protection of personal health information in telemedicine in the MERCOSUR - Lafferrière, Jorge Nicolás (2014)
Fil: Lafferrière, Jorge Nicolás. Pontificia Universidad Católica Argentina. Facultad de Derecho; Argentina